Skills of accounting personnel implications to the performance of accounting firms in Iloilo City - Almirante, Rolan; Granada, Yllen Jan; Siaton, Shirley; Tolentino, Ramon, Jr
In this study, researchers look into relationship between the skills of accounting personnel and the perfromance of accounting firms in Iloilo City. This is to find out the true extent of the contribution of an indiividual employee to a frim;s overall effectiveness when this person's abilities are measured through the basic, higher-order thinking, affectiveness, employability and technical skills that he or she possesses. Considering the reported mismatch between employer demands and employee capabilities, it would indeed contribute to the Accountancy academic field if this study should bring to light certain aspects that must be looked into to make graduates and current employees more competitive in their careers. Specifically, the study wanted to accomplish the following: (1) To idnetify the skills possessed by personnel and prospective employees of the accounting firms in Iloilo City; (2) To know if there is a significant relationship between the skill preferences of accounting firms and the skills possessed by the employee and proospective employees of such firms; (3) To discern the extent of the contribution of such skills of accounting personnel to the performance of the firms; and (4) To provide recommendations of possible ways and means to improve accounting personnel's skills that would help improve the performance of said accounting firms. This study is likewise concerned with the extent of the contribution of the skills of accounting personnel to the performance of the accounting firms in Iloilo City. Also, influence of personal, organizational and environmental factors on these skills were assessed, so as to determine the reach of the individual's input to the overall morale, flexibility, productivity, efficiency, output quality, profitability, and competitiveness of their respective organizations/firms. The research design of this study is basically descriptive. The participants of this study consisted of accountancy students coming from different universities/colleges, and employees and employers of different accounting firms in Iloilo City. Questionnaires were utilized as survey material to find out basic and research-related information from the study's respondents. To further substantiate the study, the researchers referred to both related published and unpublished materials, the sources of which are extensive-from Iloilo City academic libraries to international studies posted by academicians on the Internet. The respondents were as follows: 125 accounting students, 8 accounting firm employers and 48 accounting firm employees. The researchers concluded that all of the employers from the sample population wanted to have employees or applicants who possess not lower than their perceived high level of basic, Affectiveness, Higher-Order Thinking, Communication and Relating, and Technical skills. The study showed that only a few percent, going as high as only 10 (ten) percent, of the personnel and student respondents believe that they possess very high levels of any of the above-mentioned skills. Further, the results showed that the employers' demand for workers with a good range of high level skills are poorly met by the personnel and applicants.In most of the skill aspects, majority of personnel and student believed themselves to be only moderately proficient. None of the employers and employees wanted or possessed low levels of proficiency in any of the aforementioned skills area. However, it is to be noted that at least 5 (five) percent of the students from the sample population believed that they possessed low levels of some of the above-mentioned skills. In most of the factors that contribute to the morale and motivation of employees, productivity and effectivity, flexibility and competitiveness, both the employers' and employees' views coincided. In terms of personal, organizational and environmental intervening factors, it is shown that these have a significant influence on the work performance fo accounting firm employees, as perceived by the employees and the personel themselves. All three factors pose either high or moderate influence on employee work performance, but personal intervening factors overall have the greatest influence on the personnel, with most of the individual personal areas ranking mostly high or very high in terms on influence on the workers. on the part of employees and prospective employees (students), the researchers recommend them: (1) To further take steps to enhance their basic, affectiveness, high order thinking, communication and relating, and technical skills so as not to only come up to the high expectations of employers, but to stay ahead in the highly competitive job market; (2) For students who perceived themselves to have low proficiency in certain skills areas should make it a point to improve on these weak points; and (3) For employees, who are perceived by employers to contribute to the firm the most with the correctness of their output, should make it a point to maintain strict standards of work integrity and output efficiency. On the part of the employers, the researchers reiterate that skills enhancement is necessary for the workers of an accounting firm to be able to thrive in the competitive, ever changing, demanding and modern business community. Employers should keep in tune with the latest work systems, technology and workplace practices and make it a point of updating workers with these. For the board of Accountancy and schools that offer Accounting/degrees, overall skill enhancement must be given in curricula and in the subject matter being taught. Versatile individuals must be cultivated, not only highly proficient accountants who possess high level technical skills and nothing more. In today's highly competitive and fast-paced business industry, skills of all kinds are demanded from those who are part-the ability not only to understand and do business, but also to interact within the business. One must be well-rounded in order to do well in this sort of environment that demands for individual dynamism.